2020
DOI: 10.3389/fendo.2020.00558
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phenotype of Germline Pathogenic Variants in MAX: Concurrence of Pheochromocytoma and Ganglioneuroma in a Chinese Family and Literature Review

Abstract: Background: MYC associated factor X (MAX) is a tumor suppressor gene and has been identified as one of the pathogenic genes of hereditary pheochromocytoma (PCC). To date, there have been no reports of ganglioneuroma (GN) with MAX variants. Case Presentation: The proband was a 45-years-old Chinese female with paroxysmal hypertension and palpitations who had undergone adrenalectomy for PCC 14 years ago. Her plasma free normetanephrine and 24-h urinary norepinephrine excretion were significantly increased, and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…MAX has been recently described at a total of~40 PPGLs (9,(32)(33)(34). In our study, 6 patients had MAX variant, with the ratio being 1.9% in all PPGL patients.…”
Section: Discussionsupporting
confidence: 52%
“…MAX has been recently described at a total of~40 PPGLs (9,(32)(33)(34). In our study, 6 patients had MAX variant, with the ratio being 1.9% in all PPGL patients.…”
Section: Discussionsupporting
confidence: 52%
“…Among 499 studies, 213 articles reported variants related to PPGLs and 16 papers reported MAX variants. We summarized the characteristics of the cases with PPGLs in MAX variants [ 5 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Supplementary Table S1 ). Combining data from the 16 reports in MAX variants revealed that 42/71 cases (59.2%) had bilateral PCCs, 9/59 cases (8.5%) had PGLs, and 31/70 cases (44.3%) had an apparent family history of PPGLs.…”
Section: Discussionmentioning
confidence: 99%